Structural and functional aspects of membranes The involvement of lipid rafts in Alzheimer's disease pathogenesis. The interplay between protein oligomers and plasma membrane physicochemical features in determining cytotoxicity - Evangelisti, Elisa (Premio Tesi di Dottorato, 2013)
Alzheimer's disease (AD) is a common form of dementia characterized by the formation of extracellular senile plaques composed of aggregated amyloid peptide (Aβ). The present studies provide evidence that: cell resistance to amyloid toxicity is related to lipid raft cholesterol content. Cholesterol and GM1, affect the susceptibility of Familial Alzheimer's Disease (FAD) broblasts to Aβ42 oligomers in opposite ways, by modulating amyloid binding to lipid rafts and its subsequent toxic effects. The degree of toxicity of the oligomeric species results from a complex interplay between the structural and physicochemical features of both the oligomers and the cellular membrane. Neuronal differentiation of human mesenchymal stromal cells increases their resistance to Aβ42 aggregate toxicity.